The development, implementation and evaluation of a mental skills training programme for rowers at Rhodes University - Wentworth, Tara E (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
In the ever increasingly competitive world of sport, there is a pressing need for training methods that have the potential to improve the performance of athletes. It is for this reason that practices associated with sport psychology (such as mental skills training) have increased in popularity. This desire for improved performance has seen a rising number of athletes seeking out the assistance of sport psychology methods. In this research, a mental skills training (MST) programme was developed and implemented into the training regime of Rhodes University rowers in Grahamstown, South Africa. The process of this research adhered to the Organisational Development Process Model's format. Information collected from focus groups and performance profiling were utilised to design a MST programme tailored to the context of this group of athletes. This programme was implemented over one month and comprised of theoretical and practical sessions focussing on the topics of goalsetting, arousal regulation and imagery. After the programme had been completed, the participants evaluated the process in the form of individual interviews and were required to repeat the initial performance profile exercise. The results gathered from the various assessment and evaluation measures were used to compare and add to existing literature regarding MST and related disciplines. The benefits and effects of the programme have been detailed, and recommendations have been made which could possibly answer to the limitations of this research. These recommendations could provide insight into the manner in which MST programmes could possibly be more effectively implemented in future.
Keywords: Uncatalogued